The power of political voice: women's political representation and crime in India 2010-2015 - Lakshmi Iyer (UK Data Service, 2020)
The data consists of records of reported number of crimes at the district and state level from various issues of the “Crime in India” publications of the National Crime Records Bureau (NCRB) at the Ministry of Home Affairs, for the period 1985-2007. It also consists of annual data on the number of arrests made for each crime category. Data on the representation of women in legislature and local government is compiled from different sources including the electoral commission of India. The project uses variation in the timing of political reforms in India to compile some evidence of the effect of increased representation of women in local government on socio-political issues such as crime. Different forms of political representation are examined and reported in the data as well as in the main findings of the project.